MARKED ACANTHOCYTOSIS ASSOCIATED WITH KLIPPLE-TRENAUNAY SYNDROME - Ali, Syeda Mah; Raza, Naila; Aftab, Eraj; Faisal Mohammad, Mahnoor (Journal of Ayub Medical College Abbottabad, 2023)
Klipple-Trenaunay syndrome (KTS) is an extremely rare congenital vascular disorder with poorly defined incidence and prevalence. We report a case of a patient who presented after road traffic accident with primary complaints of poor wound healing and persistent bleeding from wound site. Discernible presence of arteriovenous malformation and skin hypertrophy since birth lead to the diagnosis of Klipple-Trenaunay syndrome (KTS). There was an incidental finding of acanthocytosis on peripheral film of blood which remained elevated even after clinical improvement of the patient. This case report highlights a close association of marked acanthocytosis of red blood cells and Klipple-Trenaunay syndrome.